E-Logistic Optimization For MSME’s To Prepare the New Normal Era (Conceptual Framework) - Rio Wiranto; Ridwan Sanjaya (Journal of Business and Technology, 2022)
The rapid development of technology in Indonesia due to the Covid-19 pandemic for the past two years has triggered a movement to change business models into e-commerce, including MSME units. This will certainly affect the logistics sector where this sector is one of the most important parts of e-commerce. Therefore, this scientific article aims to explain the optimization of e-logistics for MSMEs to prepare for the new normal era. This scientific article uses the literature review method with a conceptual framework that is expected to facilitate the reader and provide managerial and academic benefits. The results of the literature review that have been reviewed by the researcher showed that there is a need for supporting aspects of information and communication technology (ICT) to support the optimization of e-logistics for MSME units. The implementation of these aspects is divided into two categories, specifically for micro and small-medium enterprises